Employability of the psychology community in Malaysia - Ke, Guek Nee; Zuhrah Beevi,; Rozainee Khairudin,; Edina Salem, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Malaysian Psychological Association (Persatuan Psikologi Malaysia; PSIMA), through the Bureau for National Development, studied the employability landscape of the psychology community in Malaysia. This study investigates the psychology communities' demographic particulars, academic history, interest in pursuing postgraduate studies, and employment details. A cross-sectional design, with an online survey link, was sent to all psychology communities' networks in Malaysia, including students, practitioners, and academicians. Two versions of this electronic survey were made available, one in English and one in Bahasa Malaysia. Participation was voluntary, and data was collected anonymously. A total of 601 responses were collected. Among 402 working respondents, 200 respondents (50%) worked in the public sector, 181 respondents (45%) worked in the private sector, 18 respondents (4%) worked in non-governmental organizations (NGOs), and three respondents (1%) worked in statutory bodies. In term of income, the majority of respondents had an annual income of RM 30,001 – RM 60,000 (N=121) and RM 60,001 – RM 120,000 (N=127). The statistics also show an increase in income is positively linked to years of experience, education qualification, and work sector. Four implications can be drawn; first, this study is an inaugural study to map the present employability landscape of Malaysia's psychology community; second, the results indicate the direction of the future psychologist workforce; third, decision-makers need to reflect on the preparedness of the supply-demand of the psychology workforce in the national context, and lastly, the ‘Psychology Act’ is crucial to mitigate the country's psychology professional issues towards a top-notch psychological service in the world.